6° Seminario Internazionale di Studi sulla Ricerca Empirica in Educazione: «Le nuove frontiere della ricerca: il ruolo dei Big Data e dell'Evidence Based per gli studi interdisciplinari in campo educativo» - Concetta La Rocca (LED Edizioni Universitarie, 2016)
The 6th scientific seminar, held June 24, 2016, was organized by the Journal of Educational, Cultural and Psychological Studies. The topic was the use of Big Data and Evidence Based in education, with the aim of promoting a reflection on issue of usability, in empirical research in education, of large databases available on the Internet. The seminar was divided into two sessions concerning the lectures on the proposed theme, and an interdisciplinary round table. The opening was attended by Mario Panizza, Rector of Roma Tre University, Pasquale Basilicata, General Manager and Lucia Chiappetta Cajola, Head of the Department of Education; they welcome the initiative considered a valuable opportunity to reflect on the cultural richness generated by the enormous availability of informations, keeping firm the dutiful scientific knowledge to analyze and use the data in a critical and responsible way, and to reconcile the complexity of the information with the particularity of lived experiences. The topics covered in the study day seem to bring out an extremely complex perspective of reflection that in some ways can be traced to what Sellars, at the end of the last century, has called the «myth of the given», that represented the need to understand if the data can actually be used only for the purposes of observation, or if they can be used to make inferences with cognitive meaning.